Views of Omani Jurists on the Dismissal of Imam Al Salt Al Kharousi: From Se’al’s Meeting to the Rustaq’s Meeting among (272-1034 AH/885-1624 AD) - Alkhatri, Khulood; Alriyami, Ali (Al-Adab Journal, 2022)
Views of Omani Jurists on the Dismissal of Imam Al Salt Al Kharousi: From Se’al’s Meeting to the Rustaq’s Meeting among (272-1034 AH/885-1624 AD) This study aims to track the stances of the Ibadi Imams and Scholars regarding the dispute related to the issue of dismissal of Imam Salt bin Malik Al Kharusi in (272 AH/885 AD), as well as identifying the attempts to avoid controversy and dispute. It also attempts to highlight the most prominent meetings that the Imams and Scholars called for and their associated results. The study includes five main sections. The first section introduces the issue of dismising Imam Al Salt Bin Malik Al Kharousi and the stance taken by Musa bin Musa al-Azki and Rashid bin al-Nadhar al-Yahmadi regarding this issue. The second section adresses the Se’al’s meeting to stop the debate on the issue of removing Imam Al Salt bin Malik. The third section focuses on Nizwa’s meeting on the same issue, while the fourth section discussed the efforts of Imam Rashid bin Saeed Al-Yahmadi (425-445 AH) to stop debating this issue through the Sony meeting. The fifth section deals with the stances taken by the Ibadi Imams and Scholars on this issue between the death of Imam Rashid bin Saeed and the establishment of the Ya'rubi dynasty (445-1034 AH). The conclusion of the study included the most important results.